Nutritional status of pre-school children among BRAC member and eligible non-member households - Tarannum, Sabah; Hyder, S.M. Ziauddin; Chowdhury, AMR (BRAC Research and Evaluation Division (RED), 2019)
The study aimed at describing determinants of nutritional status of the pre-school children in BRAC member and eligible non-member households. The data were obtained from 9~840 children aged less than S years from April 1994 through December 1996 . residing in 100 villages of 3 rural thanas (sub-districts) namely Saturia, Santhia and Mirzapur. The findings showed that overall prevalence of stunting and wasting was 62% and 18~·(, respectively. i Significantly lower proportion of female compared to male children 9.-·c-e stunted (p<O.OOl). There was no significant sex difference in the proportion of wasting. The prevalence of stunting was lower among children in BRAC member compared to non-member eligible households (62% vs. 66%) (p<O.OS). The prevalence of stunting and wasting was significantly associated with point prevalence of diarrhoea and acute respiratory infection ( .... 1\R.I) (p<O.Ol). Prevalence of wasting was significantly associated with vitamin A capsule coverage and place of defecation (p<O.Ol). Children (45~o) who belonged to female headed households were less stunted compared to male headed households (640fo). Prevalence of stunting was significantly associated with family size and parent's literacy (p<O.Ol). In case of families, whose main earners were non-labour, prevalence of stunting was lower compared to manual labour households. Prevalence of stunting and wasting was significantly associated with Seasonality (p<O.Ol). Prevalence of stunting and wasting was significantly higher among non-member eligible households compare to BR.AC member households. It is necessary to create awareness about nutrition all over the country, especially focused on rural community. More emphasis should be given on nutrition, health and hygiene among rural population for nutritional well-being